Coastal dunes of the Baltic Sea shores: a review - Łabuz, Tomasz Arkadiusz; Grunewald, Ralf; Bobykina, Valentina; Chubarenko, Boris; Česnulevičius, Algimantas; Bautrėnas, Artūras; Morkūnaitė, Regina; Tõnisson, Hannes (Quaestiones Geographicae, 2019)
The article summarises results of studies conducted along the Baltic Sea sandy coasts by scientists involved in coastal dune research, and presents an attempt to describe the types and distribution of dune coasts. The Baltic Sea coasts feature lower and higher foredunes. The lowland behind the coastal dune belt is covered by wandering or stabilised inland dunes – transgressive forms, mainly parabolic or barchans. The source of sediment for dune development includes fluvioglacial sands from eroded coasts, river-discharged sand, and older eroded dunes. Due to the ongoing erosion and coastal retreat, many dunes have been eroded, and some are withdrawing onto the adjacent land. There are visible differences between the south-eastern, western, and northern parts of the Baltic Sea coast with respect to dune development. The entire southern and eastern coast abounds in sand, so the coastal dunes are large, formerly or currently wandering formations. The only shifting dunes are found at the Polish and the Russian–Lithuanian coasts on the Łebsko Lake Sandbar as well as on the Vistula and Curonian Spits. The very diverse shoreline of the south-western coast experiences a scarcity of larger sandy formations. Substantial parts of the Baltic Sea sandy coasts have been eroded or transformed by humans. The northern part of the Baltic Sea coast features mainly narrow and low sandy coasts (e.g. in Estonia). Further north, sandy dunes are virtually absent.